Determinant of Employee Performance and Organizational Commitment as an Interverning Variable - Rahayu, Lia; Panjaitan, Saur (PINISI Discretion Review, 2025)
This study aims to analyze the influence of burnout and turnover on employee performance, with organizational commitment as a mediating variable in J&T Express Bekasi Regency. A quantitative approach was used in this study, with a survey method and questionnaire distribution to 161 respondents taken using the Slovin method. The results of the study show that burnout and turnover have a significant influence on employee performance both directly and through organizational commitment. Burnout tends to decrease employee performance due to physical, emotional, and mental fatigue faced, while turnover reflects the challenge of maintaining workforce stability. Organizational commitment plays an important role as a mitigation factor in maintaining optimal employee performance. This research makes a theoretical contribution to the human resource management literature, as well as practical recommendations for J&T Express to improve employee performance through strategies that support organizational commitment and reduce burnout and turnover rates.